2020
DOI: 10.1155/2020/8875257
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency as a Predictive Factor of Transient Hypocalcemia after Total Thyroidectomy

Abstract: Background. Total thyroidectomy (TT) is recommended in the treatment of malignant and benignant thyroid diseases, and, to date, transient hypocalcemia is the most frequent complication after the procedure. We prospectively evaluated the role of vitamin D deficiency as a predictor of postoperative hypocalcemia. Methods. This is a prospective cohort study which was conducted between January 2016 and April 2019. A total of 177 consecutive patients (141 (79.7%) women and 36 (20.3%) men) who underwent TT were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
2
17
1
Order By: Relevance
“…Filippo et al reported a nearly 3-fold higher hypocalcemia risk in patients who underwent total thyroidectomy than in patients who underwent lobectomy [ 18 ]. Vitamin D plays a pivotal role in regulating calcium metabolism, and a recent study showed a significant association between postoperative hypocalcemia and low preoperative vitamin D levels in patients after total thyroidectomy [ 19 ]. Many studies have reported on the correlation between vitamin D deficiency and decreased clinical pregnancy and live birth rates after IVF/ICSI [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Filippo et al reported a nearly 3-fold higher hypocalcemia risk in patients who underwent total thyroidectomy than in patients who underwent lobectomy [ 18 ]. Vitamin D plays a pivotal role in regulating calcium metabolism, and a recent study showed a significant association between postoperative hypocalcemia and low preoperative vitamin D levels in patients after total thyroidectomy [ 19 ]. Many studies have reported on the correlation between vitamin D deficiency and decreased clinical pregnancy and live birth rates after IVF/ICSI [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 115 observational studies of bilateral thyroid surgery, age was not significantly associated with postoperative transient hypocalcemia, while female gender and Graves' disease were independent risk factors [ 20 ]. Several studies have suggested that autoimmune thyroiditis and higher cancer stages could be related to a higher risk of postoperative hypoparathyroidism, but there are conflicting reports [ 4 , 9 , 11 , 20 ]. In our study, gender, age, Hashimoto's thyroiditis, tumor size, and N stage were not significantly associated with postoperative hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that low preoperative 25OHD was associated with postoperative hypoparathyroidism or hypocalcemia [ 11 , 21 23 ]. Bove et al [ 11 ] analyzed clinical and lab data of 177 patients who underwent total thyroidectomy and found preoperative vitamin D deficiency (<25 ng/mL) was an independent risk factor in the development of hypocalcemia (OR: 14.8, 95% CI: 1.59–59.70, p = 0.012). Recently, a meta-analysis was published by Vaitsi et al [ 24 ] which included 39 observational studies of patients undergoing thyroidectomy with preoperative vitamin D status and postoperative hypoparathyroidism data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations